2021
DOI: 10.1021/acs.jpcc.0c09616
|View full text |Cite
|
Sign up to set email alerts
|

Modified Graphene Sheets as Promising Cathode Catalysts for Li–O2 Batteries: A First-Principles Study

Abstract: The Li–O2 battery is a promising energy storage device; however, it is seriously hindered by the sluggish chemical reaction of cathode catalysts. Here, we study a cathode catalyst based on B- and N-doped and BN codoping on Stone–Wales defect graphene (SWG) by first-principles calculations. Interestingly, BN codoped structure not only increases the stability of the system but also exhibits extremely low discharge and charge overpotentials. The corresponding value of overpotential for the oxygen reduction reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…It has been known that graphene is highly inert due to its delocalized π electrons. , The high ORR activity of 2D biphenylene can be rationalized from its unique electronic structures. As shown in Figure S4, the electrons are redistributed on the surface of 2D biphenylene.…”
mentioning
confidence: 99%
“…It has been known that graphene is highly inert due to its delocalized π electrons. , The high ORR activity of 2D biphenylene can be rationalized from its unique electronic structures. As shown in Figure S4, the electrons are redistributed on the surface of 2D biphenylene.…”
mentioning
confidence: 99%
“…From our experimental observations, it is most likely that the outmost layer of MoS 2 was partially converted to MoN during the nitridation process, and thus our DFT model is composed of a top MoN layer laid over the MoS 2 substrate (Figures S8–S10). Previous studies have shown that the nucleation and growth of Li 2 O 2 are largely governed by the solvation of the LiO 2 intermediate in competition with its surface absorption on the catalytic scaffolds, [46] which is closely related to the Gutmann donor number of the electrolyte and the adsorption energy (Δ E ads ) of LiO 2 [47,48] . As shown in Figure 6(a–c), the MoS 2 (002)/MoN(200) heterostructure manifests a stronger LiO 2 binding energy (Δ E ads =−10.73 eV) than the single‐component MoS 2 (Δ E ads =−7.02 eV) and MoN (Δ E ads =−6.07 eV), supporting the preferential binding of the LiO 2 intermediate on the heterostructure, followed by the subsequent surface growth of Li 2 O 2 .…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies have shown that the nucleation and growth of Li 2 O 2 are largely governed by the solvation of the LiO 2 intermediate in competition with its surface absorption on the catalytic scaffolds, [46] which is closely related to the Gutmann donor number of the electrolyte and the adsorption energy (ΔE ads ) of LiO 2 . [47,48] As shown in Figure 6(ac), the MoS 2 (002)/MoN(200) heterostructure manifests a stronger LiO 2 binding energy (ΔE ads = À 10.73 eV) than the singlecomponent MoS 2 (ΔE ads = À 7.02 eV) and MoN (ΔE ads = À 6.07 eV), supporting the preferential binding of the LiO 2 intermediate on the heterostructure, followed by the subsequent surface growth of Li 2 O 2 . This is mainly due to the electron-pulling effect from MoS 2 on MoN after the two components are brought into intimate contact, as witnessed by the calculated differential charge density profile of the MoS 2 / MoN heterostructure shown in Figure 6(d).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Shi group 27 used carbon fibers coated with nanoporous gold to strengthen the adsorptive ability of Li ions, leading to a uniform Li deposition. As for cathode, carbon-based materials 28,29 are considered the most potential cathode materials for Li-O 2 batteries to date because of their good conductivity, low cost, easy pore-formation, and good ORR activity. 30,31 However, due to deficient OER activity, it is difficult for pure carbon electrodes to play a unique role in high-performance Li-O 2 batteries.…”
Section: Introductionmentioning
confidence: 99%